SOCIAL THEORY OF INTERNATIONAL POLITICS: the impact of social constructivism in international politics Alexander Wendt - Barros, Marilene (EVOCATIO: Revista luso-brasileira de Filosofia, Artes e Cultura - ISSN: 2965-4254, 2021)
Following the structure of Wendt’s book, I will present in this article the main arguments of his social theory, and then explain how Wendt applies them to international politics. This account will render a critique those points to the problems and promises of Wendt’s social constructivism. I argue that despite flaws in his constitutive approach, his focus on the domestic-international aspect of agency and its relation to structure (of the state system) renders a significant contribution to international relations (IR) theory. Wendt calls attention to the importance of the social context within which states relate to each other and introduces an idealist perspective to the interactions of states and the interests derived from this interaction. In his constructivist challenge to IR theory (in particular Waltzian Neorealism), Wendt affirms that the distribution of power and material capabilities are not the center of international politics, and that the individualistic ontology of Neorealism should be replaced by a more holistic approach that emphasizes the way in which ideas shape identities and, consequently, the interests of states.